2019
DOI: 10.15252/emmm.201910892
|View full text |Cite
|
Sign up to set email alerts
|

What is normal? Apelin and VEGFA , drivers of tumor vessel abnormality

Abstract: In this issue of EMBO Molecular Medicine , Uribesalgo and coworkers show that high Apelin expression correlates with poor survival in advanced breast ( MMTV ‐ NeuT ) and lung ( KRAS G12D ) murine tumor models as well as in breast and lung cancer in humans. Combining Apelin inhibition (genetically or using an inactive Apelin agonist) with anti‐angiogenic therapy using different small molecular weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 9 publications
(13 reference statements)
1
10
0
Order By: Relevance
“…The results of our study fit with previous in vivo observations made, where ectopic apelin overexpression enhanced angiogenesis and tumor cell proliferation in subcutaneous tumor models [26,48,49]. Moreover, recent results obtained in a mouse model of breast cancer showed that loss-of-APLN markedly reduced tumor angiogenesis leading to impaired tumor growth and, consequently, improved survival of these animals [50,51].…”
Section: Discussionsupporting
confidence: 91%
“…The results of our study fit with previous in vivo observations made, where ectopic apelin overexpression enhanced angiogenesis and tumor cell proliferation in subcutaneous tumor models [26,48,49]. Moreover, recent results obtained in a mouse model of breast cancer showed that loss-of-APLN markedly reduced tumor angiogenesis leading to impaired tumor growth and, consequently, improved survival of these animals [50,51].…”
Section: Discussionsupporting
confidence: 91%
“…Apelin is an emerging endogenous ligand, which has attracted the attention of researchers because of its role in angiogenesis [9,13,14,26]. Previous studies have revealed that Apelin expression is up-regulated in various human solid tumors [13,26].…”
Section: Discussionmentioning
confidence: 99%
“…The bioactive peptide Apelin is an emerging endogenous ligand, which binds to the human G proteincoupled receptor APJ [8]. Apelin is a member of the adipokine family that is secreted by adipose tissue, and its expression is also observed in various cell types [9]. The Apelin gene encodes a prepropeptide consisting of 77 amino acids that may promote proteolytic maturation and subsequently generate different bioactive peptide fragments: Apelin-17, Apelin-36 and Apelin-13 that are the predominant types in the human plasma [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations